Eosinophils from eosinophilic oesophagitis patients have T cell suppressive capacity and express FOXP3. (6th December 2016) - Lingblom, C.; Wallander, J.; Ingelsten, M.; Bergquist, H.; Bove, M.; Saalman, R.; Welin, A.; Wennerås, C.
Summary: Eosinophilic esophagitis (EoE) is an antigen‐driven T cell‐mediated chronic inflammatory disease where food and environmental antigens are thought to have a role. Human eosinophils express the immunoregulatory protein galectin‐10 and have T cell suppressive capacity similar to regulatory T cells (Tregs ). We hypothesized that one function of eosinophils in EoE might be to regulate the T cell‐driven inflammation in the oesophagus. This was tested by evaluating the suppressive capacity of eosinophils isolated from the blood of adult EoE patients in a mixed lymphocyte reaction. In addition, eosinophilic expression of forkhead box protein 3 (FOXP3), the canonical transcription factor of Tregs, was determined by conventional and imaging flow cytometry, quantitative polymerase chain reaction (qPCR), confocal microscopy and immunoblotting. It was found that blood eosinophils from EoE patients had T cell suppressive capacity, and that a fraction of the eosinophils expressed FOXP3. A comparison of EoE eosinophils with healthy control eosinophils indicated that the patients' eosinophils had inferior suppressive capacity. Furthermore, a higher percentage of the EoE eosinophils expressed FOXP3 protein compared with the healthy eosinophils, and they also had higher FOXP3 protein and mRNA levels. FOXP3 was found in the cytosol and nucleus of the eosinophils from both the patients and healthy individuals, contrasting with the strict nuclear localization of FOXP3 in Tregs . To conclude, these findings suggest that the immunoregulatory function of eosinophils may be impaired in EoE. Abstract : Eosinophils in the blood of patients with eosinophilic esophagitis have T cell suppressive capacity although it seems to be impaired compared with healthy control eosinophils. FOXP3 protein and mRNA is upregulated in the eosinophils of eosinophilic esophagitis patients, where it seems to act as an activation marker.